An analysis of the policy coverage and examination of environmental-impact topics - Sikhulile Bonginkosi Msezane (Environmental Association of Southern Africa, 2017)
Environmental education and education for sustainability are educational responses to negative environmental impacts both locally and globally. In South Africa, the schooling sector has experienced several shifts in the curriculum since 1994, with implications for the coverage, teaching and examination of environmental-impact topics in subjects such as Life Sciences, Physical Sciences, Life Orientation, Agricultural Sciences, and Geography. The aim of the research reported here was to investigate the coverage and examination of environmental-impact topics in the Further Education and Training (FET) Phase of the South African school curriculum. Data sources were the Curriculum and Assessment Policy Statement (CAPS) documents and examination papers. In analysing the coverage and examination of environmental-impact topics, thematic content analysis was used. The findings indicate that there is unequal coverage of environmental-impact topics in the curriculum, despite the CAPS indicating that environmental content should feature in all subjects. The present paper shows that Life Sciences has the widest coverage and that Geography examination papers sometimes exceed the policy allocation. Agricultural Sciences has the least coverage. The study also found that there is general, but not complete, alignment between policy and examination papers. The study concluded that there is too little focus in the FET curriculum on environmental education and warns that this will constrain the development of a pro-environmental culture among learners. This has relevance for curriculum and policy developers in responding to societal and environmental issues.